Foliar stomata characteristic of fabaceae family in University of Sumatera Utara (USU) green space. Issue 1 (1st June 2022) - Susilowati, A; Ginting, I M; Kaban, N S; Rachmat, H H; Iswanto, A H; Sucipto, T
Abstract: The existence of green open space becomes important along with the decline in environmental quality. The University of Sumatera Utara (USU) campus, as one of the city's green open spaces, is expected to be able to minimize negative impacts of increasing levels of pollution. For this reason, it is necessary to select tree species to maximize the function of green open spaces. The purpose of this research was to identify the Fabaceae family's stomata characteristics, which included the type, length, thickness, and its density. To determine stomata characteristics, the epidermal layer of the leaves was perforated using nail polish. The results showed that all of observed trees had paracytic stomata with a random distribution pattern. The longest stomata was found in Erythrina crista that reached 20.15 μm in length, while the shortest stomata was found in Intsia bijuga and reached 12.36 μm in length. Tamarindus indica had the widest stomata, reaching 2.59 μm in width, while Pithecellobium dulce variegate have had smallest, at 7.74 μm in width. Peltophorum pterocarpum had the highest density at 718.68μm, while Leucaena leucocephala have had lowest density at 94/ μm 2 .